Chairside administrated antibacterial hydrogels containing berberine as dental temporary stopping for alveolar ridge preservation. (5th November 2021) - Zeng, Jia; Mamitimin, Mukaram; Song, Ya; Sun, Weibin; Wu, Zhenghong; Qi, Xiaole
Graphical abstract: Highlights: Chairside used antibacterial hydrogel was designed as dental temporary stopping. BBR/MS-CGD hydrgel was constructed based on CS crosslinked by DF-PEG and β-GP. BBR/MS-CGD achieved satisfied thermosensitive, shapeable and self-healing properties. BBR and BBR microspheres are embedded for bacterial inhibition. Osteogenic differentiation ability of BBR/MS-CGD was found to be improved. Abstract: Bone substitutes and biological materials are commonly employed in alveolar ridge preservation after tooth extraction. Here, we established a novel chairside administrated antibacterial hydrogel system as dental temporary stopping, based on chitosan (CS) crosslinked by dialdehyde-functionalized polyethylene glycol (DF-PEG) and β -glycerophosphate disodium salt hydrate ( β -GP). In addition, free berberine (BBR) and BBR microspheres are embedded into the gel for osteogenic differentiation and bacterial inhibition. We demonstrated that those gels could exhibit satisfied thermosensitive, shapeable and self-healing properties in vitro and in vivo . Besides, the long-acting sustained releasing for 20 days and antibacterial behaviors for 14 days of BBR was demonstrated. The osteogenic differentiation ability of BBR/MS-CGD gels for 21 days was found to increase 3.63 times higher than that of saline treated group, evaluated by alizarin red staining experiment. Overall, those gels offered an easily operated, chairside administrated, and personally tailored dental temporary stopping, achieving potential bacteriostatic and mineralization-promoting effect.